Is the World Flat? - Cristian Incaltarau; Gabriel-Andrei Donici (CES Working Papers, 2010)
Globalization became more and more prominent during the last decades. There is no way to argue that globalization led to more interconnected economies, facilitating the communication and the collaboration around the world. But where is this going? Doesglobalization mean uniformity or diversity? As the world begins to resemble more, the people are trying to distinguish between them more, which can exacerbate nationalistic feeling. Friedman argues that globalization made the world smaller and flatter, allowing all countries to take chance of the available opportunities equally. But is this really true? Although politic and cultural factors can stand in front of a really flat world, what is the key for Chinese and Indian success and which are theirs perspectives?
Keywords: 330; flat world; flattener; globalization; nationalism; China; India; communication; technology; emerging economy; education